Structural modal reanalysis for large, simultaneous and multiple type modifications. (October 2015) - Jian-jun, He; Xiang-zi, Chen; Bin, Xu
Abstract: Eigenvalue problem is widely used to investigate the dynamic characteristics of large and complex structure. For finite element models, iterative solvers are needed to precisely calculate eigenvectors and eigenvalues. However, in cases such as large-scale reanalysis studies, or optimization design of huge structure, computational cost can quickly become too time consuming. This paper focus on the structural modal reanalysis for large and multiple modifications (including simultaneous boundary, topology and type modifications), which can greatly affect the eigen-modes of the modified structures. The proposed methods are based on the results from the modal analysis of the original structure, and the stiffness and mass matrix of the modified structures. A highly approximate eigensolution are generated by the proposed method, which is combined the newly added DOF (Degrees of Freedom) condensation, ICMO strategy (Independent and Coupling Mass Orthogonalization) with the Rayleigh–Ritz analysis. The numerical examples show that the proposed method is efficient with high precision even when large and multiple type modifications of the structural topology, boundary and type are made simultaneously. Highlights: We study modal reanalysis for large and multiple type structural modifications. The structure is modified with type, topology and boundary parameters. ICMO strategy with Rayleigh–Ritz analysis is used. High quality reanalysis result was obtained for multiple type modifications.